Finite element analysis of different fixation methods of screws on absorbable plate for rib fractures - Xue, Hang; Zhang, Zhenhe; Liu, Mengfei; Lin, Ze; Endo, Yori; Liu, Guodong; Mi, Bobin; Zhou, Wu; Liu, Guohui (Frontiers in Bioengineering and Biotechnology, 2022)
Multiple rib fractures caused by trauma are a common injury and the internal fixation methods of these injuries have been paid more and more attention by surgeons. Absorbable plates and screws are the effective way to treat rib fractures, but there are no reports on which type of screw fixation method is most effective. In this study, finite element analysis was used to study the effects of five different types of screw fixation methods on anterior rib, lateral rib and posterior rib. The finite element model of the ribs was reconstructed from CT images, and the internal pressure (40 kPa) and intercostal force (30 N) on the upper and lower surfaces of the ribs were simulated accordingly. An intercostal force of 30 N was applied to the upper and lower surfaces of the ribs to simulate the effect of intercostal muscle force. The pressure of 40 kPa was applied to the inner surface of the ribs, and the normal direction was applied to the inner surface of the ribs. The positive direction was considered inspiratory pressure, and the negative direction expiratory pressure. The results indicate the optimal type of screw fixation on the absorbable plate for rib fractures, and provides a basis and reference for clinical application.